A Quantum Computer Architecture Based on Silicon Donor Qubits Coupled by Photons. Issue 11 (2nd June 2020) - Yan, Xiruo; Asavanant, Warit; Kamakari, Hirsh; Wu, Jingda; Young, Jeff F.; Raussendorf, Robert
Abstract: A comprehensive circuit architecture and a protocol for realizing 3D cluster states through photonic‐measurement‐based donor‐spin‐qubit entanglement and readout are described. The basic building blocks and protocol are chosen to be compatible with a fully integrated photonic circuit implementation, using Se + as the photonically coupled matter qubit. The basic operational building blocks of this universal quantum computing machine are local measurements and unitaries, plus an entangling measurement of non‐local Pauli operators. By analyzing several sources of error, a theoretical fault‐tolerant threshold value is estimated on the order of 1%. Considering the literature where required components have already been realized in integrated silicon circuits, albeit not all on the same chip, this suggests the threshold is within reach. Abstract : A comprehensive circuit architecture and protocol for realizing 3D cluster states through photonic‐measurement‐based donor‐spin‐qubit entanglement and readout is described. The physical components and protocol are compatible with a fully integrated photonic circuit implementation in silicon. Analysis of the protocol suggests a fault‐tolerance threshold of  1%, which is within reach of integrated silicon photonic technology.